Identifikasi struktur dan perubahan lanskap Kota Banjarmasin di masa kesultanan (1526-1860) - Damayanti, Vera D (Jurnal Arsitektur Lansekap, 2019)
Identifying the structure and transformation of Banjarmasin townscape during the Sultanate period (1526-1860): Banjarmasin city in the past was widely known as one of the main pepper producers in the Archipelago that turned the town to becoming one of the port cities in the Southeast Asia maritime trade network. As a port city, Banjarmasin showed a typical landscape character similar to other port cities in Southeast Asia. The physical landscape feature of this city inevitably was influenced by the economic factor on which trade was the primary income of the sultanate and its people. During the Sultanate period (15261860), the landscape of Banjarmasin was transformed as an impact of the political influence that related to the pepper trade, which involved foreign traders. The main objective of this study is to analyse the landscape  changing of Banjarmasin during the Sultanate period by applying the historical method and spatial approach. In the spatial analysis, the landscape component of processes, space, material, and form was used to identify the landscape structure and its transformation. The result of the study shows that the landscape of Banjarmasin evolved in the following stages: (1) port-polity of Banjar sultanate (1526-1612); (2) secondary port-city of the sultanate (1612-1663); (3) primary port of the sultanate (1663-1787); (4) primary port of the Dutch in Southeast Kalimantan (1787-1860). With regard to the research process, the spatial dimension was not only obtained from the historical maps but also from written sources that indicated the location of activities or events.